Differences in the tensile strength of direct nanohybrid composite veneers between the V and VIII generation dentin bonding agent after extracoronal bleaching - Rizkia, Erlin Zuke; Logamarta, Setiadi Warata; Dwiandhono, Irfan (Padjadjaran Journal of Dentistry, 2018)
Introduction: Tooth discolouration is the most common esthetic problems in dentistry. Direct composite veneer is an adjunctive therapy for severe teeth discolouration by attaching to the tooth surface using an acid etching and dental bonding agent. In several cases of severe discolouration, it is required to have certain preliminary treatments such as bleaching prior to the placement of the composite veneer. However, bleaching agents are able to lead the enamels morphology and microstructure alteration by inhibiting the polymerisation bonding thus affecting the veneer adhesion. This study was aimed to determine the tensile bond strength of direct composite veneers between the V and VII generation dentin bonding agent after extracoronal bleaching. Methods: This study was an experimental laboratory of as much as 32 human permanent maxillary central incisors were divided into 4 groups. Group 1 was treated with extracoronal bleaching and bonded with the V generation bonding nanohybrid composite. Group 2 was treated with extracoronal bleaching and bonded with the VIII generation bonding nanohybrid composite. Group 3 was only bonded with the V generation bonding nanohybrid composite. Group 4 was only bonded with the VIII generation bonding nanohybrid composite. All samples were immersed in artificial saliva then incubated at the room temperature for 24 hours. Results: The tensile strength value was determined using the Universal Testing Machine. The ANOVA test results showed significant differences in all four groups (p < 0.05). Conclusion: The VIII generation bonding agent had a higher tensile strength than the V generation.